Hematopoietic Stem Cell Transplant as Symptomatic Treatment for Myasthenia Gravis: A Literature Review - Sutrisno, Jessica Amadea; Andryani, Yani; Devinda, Ni Luh Airin Gita (Future Science, 2025)
Myasthenia gravis (MG) is an autoimmune neurological disorder that impairs communication at the neuromuscular junction. Over the past seven decades, its global incidence has steadily increased. Approximately 10–20% of MG patients do not respond adequately to or cannot tolerate conventional treatments. Hematopoietic stem cells (HSCs), which are multipotent cells capable of producing all blood cell types and restoring the hematopoietic system, are being explored as a therapeutic option. Hematopoietic stem cell transplantation (HSCT) is under investigation as a potential treatment for severe and refractory MG, with ongoing research aimed at enhancing its safety, and efficacy, and identifying optimal candidates for the therapy. This paper aimed to evaluate the efficacy of hematopoietic stem cell transplantation (HSCT) as a therapeutic option for managing symptomatic myasthenia gravis (MG), especially in cases unresponsive to conventional therapies. A systematic search identified five studies, comprising two cohort studies and three case reports. Most patients in these studies demonstrated promising improvement following HSCT treatment, as indicated by a reduction in MGFA scores and improved clinical manifestations during follow-up assessments. This treatment approach has demonstrated significant potential. However, the current studies are susceptive to bias, and more preclinical research along with high-quality clinical trials, large-scale are required to determine if this emerging treatment can meet the anticipated outcomes.